Treatment of an oral malignant lesion following mucosal insult; a case report - Zilefac Brian Ngokwe; Ntep Ntep David Bienvenue; Aminkeng Azicha Shannen; Nokam Kamdem Stephane; Bola Siafa Antoine; Sando Zacharie (Elsevier, 2023)
Head and neck squamous cell carcinomas (HNSCCs) are aggressive cancers with high morbidity and low survival rates, as well as limited therapeutic options.We present the case of a 54-year-old patient, person living with HIV/AIDS (PLWH) who presented with a history of an ulcerating lesion in her soft palate following self-inflicted mucosal insult which later revealed as an invasive squamous cell carcinoma with high grade dysplasia.The patient underwent chemotherapy and demonstrated remarkable clinical recovery with complete remission of signs and symptoms.We present a case in which early diagnosis and interdisciplinary collaboration were critical in ensuring a good prognosis for the patient, who is at the moment of writing, asymptomatic.